2021
DOI: 10.1055/a-1345-0044
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic full-thickness resection of polyps involving the appendiceal orifice: a multicenter international experience

Abstract: Background and Aims: Endoscopic resection of lesions involving the appendiceal orifice (AO) remains a challenge. We aim to report the outcomes of full-thickness resection device (FTRD) for the resection of appendiceal lesions and identify factors associated with the occurrence of appendicitis. Methods: This is a retrospective study at 18 tertiary-care centers (12 U.S., Canada 1, 5 Europe) between 11/2016 and 8/2020. Consecutive patients who underwent resection of AO lesions using the FTRD were included. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 32 publications
(130 reference statements)
0
50
0
1
Order By: Relevance
“…This was indicated by significant RT differences between stay and switch trials in the weighted model. Switch costs due to changing features within a single feature dimension may be relatively small compared to cross-dimensional switch costs (see MĂĽller et al, 1995), which could explain why there was no switch effect in the averaged model in any level of awareness. Thus, the putatively smaller effect of within-dimensional switches may require a strong prior feature weighting to emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was indicated by significant RT differences between stay and switch trials in the weighted model. Switch costs due to changing features within a single feature dimension may be relatively small compared to cross-dimensional switch costs (see MĂĽller et al, 1995), which could explain why there was no switch effect in the averaged model in any level of awareness. Thus, the putatively smaller effect of within-dimensional switches may require a strong prior feature weighting to emerge.…”
Section: Discussionmentioning
confidence: 99%
“…For consciously perceived visual stimuli, such history-driven attention weighting effects have been observed in singleton search tasks. For instance, repeated presentation of the same target-defining dimension leads to response time benefits and associated activation changes in dimension-specific visual processing areas (Pollmann et al, 2006) that were interpreted as evidence for an attentional weighting of the target-defining dimension (MĂĽller et al, 1995;Liesefeld et al, 2018). In contrast, when the target-defining dimension changes, e.g., when the target was defined by a singleton color in recent trials and then is defined by a singleton motion direction, response time costs are observed, as would be expected when attention needs to be reweighted to the new target-defining dimension.…”
Section: Introductionmentioning
confidence: 99%
“…However, a nontrivial fraction of patients, 17% (95% confidence interval 9.4%-29%), did have post-EFTR appendicitis of which 60% required surgical appendectomies. 44 Therefore, this should primarily be considered in the setting of a multidisciplinary discussion of options, with transparency of this risk during the informed consent process. We would also argue that EFTR is not necessary for an appendiceal orifice polyp where all margins of the polyp are visible and accessible by other means of resection, such as hot or cold EMR.…”
Section: Polyps Unable To Be Resected With Emr or Esdmentioning
confidence: 99%
“…In recent years, endoscopic full-thickness resection (EFTR) using a specially designed EFTR device (FTRD; Ovesco Endoscopy, TĂĽbingen, Germany) has been introduced to dissect lesions involving the appendiceal orifice 6 7 8 . Although it is a single-step and non-exposure procedure, the EFTR still cannot ensure complete resection of lesions with deep invasion into the appendiceal lumen, and may lead to a higher incidence of postoperative appendicitis 6 7 8 . Surgery may be needed for some of these patients owing to postoperative perforation or intrabdominal abscess 6 7 8 .…”
Section: Introductionmentioning
confidence: 99%